110 μm thin endo-microscope for deep-brain in vivo observations of neuronal connectivity, activity and blood flow dynamics - Stibůrek, Miroslav; Ondráčková, Petra; Tučková, Tereza; Turtaev, Sergey; Šiler, Martin; Pikálek, Tomáš; Jákl, Petr; Gomes, André; Krejčí, Jana; Kolbábková, Petra; Uhlířová, Hana; Čižmár, Tomáš (Nature communications, 2023)
Light-based in-vivo brain imaging relies on light transport over large distances of highly scattering tissues. Scattering gradually reduces imaging contrast and resolution, making it difficult to reach structures at greater depths even with the use of multiphoton techniques. To reach deeper, minimally invasive endo-microscopy techniques have been established. These most commonly exploit graded-index rod lenses and enable a variety of modalities in head-fixed and freely moving animals. A recently proposed alternative is the use of holographic control of light transport through multimode optical fibres promising much less traumatic application and superior imaging performance. We present a 110 μm thin laser-scanning endo-microscope based on this prospect, enabling in-vivo volumetric imaging throughout the whole depth of the mouse brain. The instrument is equipped with multi-wavelength detection and three-dimensional random access options, and it performs at lateral resolution below 1 μm. We showcase various modes of its application through the observations of fluorescently labelled neurones, their processes and blood vessels. Finally, we demonstrate how to exploit the instrument to monitor calcium signalling of neurones and to measure blood flow velocity in individual vessels at high speeds.
Keywords: rychlost toku krve; mozek; myši; Microscopy, Confocal; Head; Animals; Blood Flow Velocity; hlava; Mice; neurony; zvířata; konfokální mikroskopie; Neurons; Brain